Atomistic investigation of the influence of hydrogen on dislocation nucleation during nanoindentation in Ni and Pd. (1st September 2016) - Zhou, Xiao; Ouyang, Bin; Curtin, W.A.; Song, Jun
Abstract: The effects of hydrogen charging on the mechanical response of FCC Ni and Pd under nanoindentation are systematically investigated by molecular dynamics simulations. Simulations consider a random H distribution and time scales prevent any diffusion of H during the simulations. Hydrogen charging is then found to reduce the threshold load for dislocation nucleation, i.e., the pop-in load, but only to a limited extent. After pop-in, the indentation response is largely independent of the presence of H. Furthermore, the influence of hydrogen charging on the pop-in load originates only from the hydrogen-induced swelling of the lattice. That is, H does not directly influence dislocation nucleation, either in terms of facilitating initial slip or interacting with the nascent dislocation(s). These findings suggest that rate-dependent processes, either associated with fluctuating nucleation or H transport, are necessary to interpret experimental observations of hydrogen-influenced reductions in the pop-in load. Graphical abstract: